Challenges and Oppurtunities for Adult Education in the Digital Era: The Role of Guidance and Counseling - Wijayanti, Lanny Ilyas; Sanyata, Sigit (Jurnal Bimbingan dan Konseling Terapan, 2024)
In the history of adult education has gone through various stages of evolution, a long history has brought the understanding that adult learning is not only about the transfer of knowledge but also involves psychological, social and cultural aspects. In the context of adult education, guidance and counseling play an important role in supporting holistic individual development. Guidance and counseling helps adults overcome challenges, set realistic goals, and develop strategies to reach potential. While the digital era presents new challenges and opportunities in the context of adult learning, literacy is not just the ability to use technology but also involves critical and creative skills in understanding and utilizing digital information. There are many positive impacts that can be enjoyed, such as efficiency and ease of access to information. The research method used is a literature review with descriptive qualitative data analysis, which aims to seek a deeper understanding of adult education, as well as digitalization and literacy. It is necessary to pay further attention to how they optimize the potential of technology in everyday life. In this way, the integration between the concepts of andragogy, digitalization, and guidance and counseling offers a holistic and integrated approach in supporting adult learning and development. By utilizing technology wisely and supported by the right guidance, individuals can optimize their potential in various aspects of life, thereby creating a society that is more skilled, competitive and digitally cultured.